2006
DOI: 10.1007/s00702-006-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for specific phases in the development of human neuromelanin

Abstract: Neuromelanin is a dark-coloured pigment which forms in the dopamine neurons of the human midbrain. Here we describe the age-related development and regulation of neuromelanin within these dopamine neurons. 10 microm sections from formalin-fixed midbrain from 29 people spanning the ages of 24 weeks to 95 years old were either stained with a basic Nissl substance stain (0.5% cresyl violet), or processed unstained. After locating the substantia nigra using the stained sections, digital photos were taken of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…By utilization of the Gene Ontology annotations 19 proteins of the differentially expressed proteins could be related to lysosomes, which underlines the lysosomal relationship of NM granule which was already previously described37. Previously knowledge23 combined with these new findings lead to the hypothetical process describing NM granules genesis depicted in Fig. 3.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…By utilization of the Gene Ontology annotations 19 proteins of the differentially expressed proteins could be related to lysosomes, which underlines the lysosomal relationship of NM granule which was already previously described37. Previously knowledge23 combined with these new findings lead to the hypothetical process describing NM granules genesis depicted in Fig. 3.…”
Section: Discussionsupporting
confidence: 54%
“…So far NM granules cannot be identified in human newborns, but seem to start forming in childhood presumably from the age of three years. From then on an increase in amount and density of NM granules can be observed during normal aging23. The physiological function of NM granules is controversial discussed in literature.…”
mentioning
confidence: 99%
“…PD showed a decrease in nigral pigmented neurons (Hirsch et al ., 1988, 1989; Fearnley & Lees, 1991), which suggested that the selective degeneration of these cells could be a feature of this illness and that neuromelanin may be involved in this degeneration (Hirsch et al ., 1988). However, healthy aged subjects also showed a decrease in pigmented cells (7-10% decrease per decade) (McGeer et al ., 1988; Ma et al ., 1999; Cabello et al ., 2002; Stark & Pakkenberg, 2004; Fedorow et al ., 2005; Halliday et al ., 2006; Double et al ., 2008; Rudow et al ., 2008), suggesting that if neuromelanin was involved in PD, it could also be involved in aging-related neurodegeneration.…”
Section: Degeneration Of Dopamine Cells In Pd and Agingmentioning
confidence: 99%
“…Neuromelanin is a byproduct of neuronal norepinephrine (NE) and dopamine synthesis, accumulating in cell bodies beginning in early childhood and increasing in concentration throughout life (Zecca et al, 2004; Halliday et al, 2006). Thus, neuromelanin is a target for biomarker development to characterize neurodegenerative diseases where low contrast is predicted to occur with LC neuron loss in older adult samples.…”
Section: Introductionmentioning
confidence: 99%